Raccontare la grazia tra Ottocento e Novecento: riflessioni preliminari su testimonianze di malattie, medici e devoti - Domenica Borriello (EtnoAntropologia, 2017)
The stories of healing from illness of late nineteenth century documenting the graces bestowed by the Virgin or a saint and votive paintings of the same period shed light on epidemic diseases, official therapies and devotional practices. The votive representations, as reports of graces received, are complementary sources that communicate both with their specific and different languages, the will to make public the grace received. Reports of graces testify other interesting aspects such as the doctor-patient relationship, the home environment with different characters and their roles, and the meaning of suffering lived in the home. The statement of a reality often based on the ambivalence of the role of the doctor and on syncretisms still detectable in the practices of medicalization is no less important.